2021
DOI: 10.21511/ppm.19(2).2021.20
|View full text |Cite
|
Sign up to set email alerts
|

The impact of firm size on the performance of Vietnamese private enterprises: A case study

Abstract: This article investigates the effect of firm size on the performance of Vietnamese private enterprises. Based on the data from the Annual Enterprise Survey from 2009 to 2018, this study uses an ordinary least-squares regression model (OLS) to point out the effects of firm size (growth rate, total assets, and total labor) on the performance of Vietnamese private enterprises in both static and dynamic states. According to the results of the quantitative model, total assets are the biggest factor for determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
9
2
2
Order By: Relevance
“…Large companies usually have advantages in terms of resources and capabilities in product development, development of technological innovation, and of course better implementation of business, marketing and e-commerce strategies (Kipesha, 2013). Another advantage of large companies is the ownership of human resources (Hung et al, 2021;Yang & Chen, 2009). They have a large workforce of highly qualified workers and can recruit skilled workers.…”
Section: Effect Of Firm Size On Firm Financial Performancementioning
confidence: 99%
“…Large companies usually have advantages in terms of resources and capabilities in product development, development of technological innovation, and of course better implementation of business, marketing and e-commerce strategies (Kipesha, 2013). Another advantage of large companies is the ownership of human resources (Hung et al, 2021;Yang & Chen, 2009). They have a large workforce of highly qualified workers and can recruit skilled workers.…”
Section: Effect Of Firm Size On Firm Financial Performancementioning
confidence: 99%
“…Secara khusus, beberapa industri (seperti perusahaan e-commerce) mungkin membelanjakan lebih banyak untuk kegiatan periklanan dan pemasaran. Perusahaan besar mungkin menghadapi inefisiensi karena beberapa kendala seperti biaya tenaga kerja, biaya terkait yang lebih besar, proses manajemen yang kompleks, manajemen birokrasi, administrasi, tingkat investasi yang tinggi, pengalihan investasi, dan lain-lain (Hung, Vinh, & Thai, 2021).…”
Section: Firm Sizeunclassified
“…They established a positive and significant relationship between firm size and the financial performance of firms. Hung et al (2021), using panel data from 2009 to 2018 in Vietnamese Private Firms, found that firm size impacted the performance of firms. Specifically, the study showed that firm size reflected by non-current assets, manpower, and output volumes are influenced by firm size.…”
Section: Control Variables (Growth In Sales and Firm Size) And Financ...mentioning
confidence: 99%